The Impact of Migraine on Posterior Ocular Structures - Süleyman Demircan; Mustafa Ataş; Sevgi Arık Yüksel; Melek D. Ulusoy; İsa Yuvacı; Hasan Basri Arifoğlu; Burhan Başkan; Gökmen Zararsız (Journal of Ophthalmology)
Purpose. To investigate the thickness of the retinal nerve fiber layer (RNFL) and choroid in patients who have migraines in comparison to healthy controls. Methods. This study included 76 eyes and patients in the migraine group, 36 with aura (MWA group) and 40 without (MWoA group), and 38 eyes as control subjects. The RNFL and macular thicknesses were analysed with standard OCT protocol while choroidal thickness was analysed with EDI protocol in all subjects. Choroidal thickness was measured at the fovea, 1500 µm nasal and 1500 µm temporal to the fovea in a horizontal section. Results. The mean RNFL thickness for nasal and nasal inferior sectors was significantly thinner (P≤0.018) in the migraineurs’ eyes than in those of the controls, as was the mean choroid thickness at the fovea and measured points (P<0.0001). However, the mean macular thickness was not significantly different between the groups. Conclusions. This study suggests that migraine leads to a reduction in the peripapillary RNFL thickness and to thinning in choroidal structures. These findings can be explained by a chronic ischemic insult related to migraine pathogenic mechanisms and these findings are considered supportive of the relationship between glaucoma and migraine.